TRAIL 매개 apoptosis 촉진 및 autophagic cell death를 통한 악성 glioma 선택적인 세포 사멸 유도 방안 연구 - 김은희 (The Graduate School, Ajou University, 2007)
Malignant gliomas, the most common brain tumors with high mortality, remain largely incurable despite multimodal treatments including surgical resection, radiotherapy, and chemotherapy. Thus, the researchers are currently attempting to develop novel therapeutic strategies for malignant gliomas. Here, we show that treatment with subtoxic doses of HDAC inhibitor (sodium butyrate, tricostatin A or SBHA) or As2O3 in combination with tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) induces rapid apoptosis in TRAIL-resistant glioma cells, but not in human astrocytes. HDAC inhibitor sensitizes human glioma cells to TRAIL-mediated apoptosis through inhibition of Cdc2 and the subsequent downregulation of surviving and XIAP, whereas As2O3 sensitizes human glioma cells to TRAIL-induced apoptosis via CHOP-dependent DR5 upregulation. Furthermore, we demonstrate that selenite is preferentially cytotoxic to various human glioma cells over normal astrocytes via autophagic cell death. In this process, selenite induces superoxide-mediated mitochondrial damage and subsequent autophagic cell death. Therefore, these results suggest that stimulation of TRAIL-induced apoptosis by co-treated HDAC inhibitor or arsenic trioxide as well as selenite-induced autophagic cell death may offer an attractive strategy for safely treating gliomas.
학위논문(박사)----아주대학교 일반대학원 :분자과학기술학과,2007. 8
Keywords: Glioma; Apoptosis; Autophagic cell death; TRAIL; HDAC inhibitor; Arsenic trioxide; Sodium selenite